2008
DOI: 10.1002/jcp.21647
|View full text |Cite
|
Sign up to set email alerts
|

S6K1 is involved in polyploidization through its phosphorylation at Thr421/Ser424

Abstract: Studies on polyploidization of megakaryocytes have been hampered by the lack of synchronized polyploid megakaryocytes. In this study, a relatively synchronized polyploid cell model was successfully established by employing Dami cells treated with nocodazole. In nocodazole-induced cells, cyclin B expression oscillated normally as in diploid cells and polyploid megakaryocytes. By using the nocodazole-induced Dami cell model, we found that 4E-BP1 and Thr421/Ser424 of ribosomal S6 kinase 1(S6K1) were phosphorylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 48 publications
(56 reference statements)
2
17
0
Order By: Relevance
“…mTORC2 modulates cells metabolism through phosphorylating Akt/PKB and activating the downstream such as FoxO3a (19,39). Furthermore, knockout of rictor (one of the mTORC2 components) in mice liver (40), adipose (19), or muscle (20) cells impaired glycolysis and lipogenesis. These studies suggested that mTOR pathway played an important role in activating cellular bio-energetic processes contributed to cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mTORC2 modulates cells metabolism through phosphorylating Akt/PKB and activating the downstream such as FoxO3a (19,39). Furthermore, knockout of rictor (one of the mTORC2 components) in mice liver (40), adipose (19), or muscle (20) cells impaired glycolysis and lipogenesis. These studies suggested that mTOR pathway played an important role in activating cellular bio-energetic processes contributed to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mTOR was associated with the development of polyploidization. Ma and colleagues showed that S6K1, a downstream of mTOR, was involved in polyploidization through its phosphorylation at Thr421/ Ser424 (20). In addition, activation of mTOR pathway was required for TSC2 þ/EK [EKer rat model carrying a germline insertional deletion in one copy of the Tsc2 (tuberous sclerosis 2) gene] smooth muscle cells of pulmonary lymphangioleiomyomatosis to undergo tetraploidization (21).…”
Section: Introductionmentioning
confidence: 99%
“…5364P). The polyclonal antibodies against EIF4EBP1, phosphoThr69-EIF4EBP1, and phospho-Ser64-EIF4EBP1 have been used extensively, and their specificity established in earlier studies (Gingras et al 2001a;Wang et al 2003;Ohne et al 2008;Ma et al 2009;Fonseca et al 2011;Fuchs et al 2011) including one report (Ellederova et al 2006) in which SDS-PAGE/Western blotting of in vitro matured pig oocytes showed specific reactions with bands of the appropriate sizes. After overnight incubation with primary antibody at 4°, the oocytes were washed three times in blocking buffer for 10 min each wash.…”
Section: Oocyte Fixation and Immunofluorescencementioning
confidence: 99%
“…Moreover, the role of S6K1 and 4E-BP1 in the polyploidization of MKs is not clearly understood. Previously, we demonstrated that S6K1 was involved in polyploidization through its phosphorylation at Thr421/Ser424 during M phase in nocodazole-treated Dami cells [7] . However, in nocodazole-induced polyploidization, the cells are multinucleated (karyokinesis is not affected), while in MKs, the nuclei are polylobulated.…”
Section: Introductionmentioning
confidence: 90%